Narasi Moderasi Beragama dalam Naskah Serat Carub Kandha - Agus Iswanto; Nurhata; Asep Saefullah (Jurnal Lektur Keagamaan, 2021)
A number of traditional historiographies are narrated in manuscripts from Cirebon, not a few that mention religious moderation. However, the babad manuscripts tend to change their perspective when it enters the Colonialism era. The narrative of tolerance between ethnic groups or between religions was experiencing serious friction. There is a manuscript that comes from the Cirebon tradition, which narrates implicitly about religious moderation in the early eras of the development of Islam and the port cities, namely Serat Carub Kandha. This article discusses three issues related to religious moderation in Serat Carub Kandha, namely: (1) the context behind the writing and copying of the Serat Carub Kandha manuscript; (2) the narrative of religious moderation in the Serat Carub Kandha; (3) Its relevance for current religious life in Indonesia. The source that was used as the primary material for the research was the Serat Carub Kandha manuscript, the collection of Rafan Hasyim in Cirebon, written by Pegon. With a philological and hermeneutic approach, this article shows that the Serat Carub Kandha manuscript is historical evidence and collective memory of the practice of religious moderation in Indonesia's past, especially on the north coast of West Java. The moderation narrative that has emerged is about respecting other religions, accommodating local culture, and anti-violence. Keywords: Babad manuscripts, Cirebon, religious moderation, Serat Carub Kandha   Sejumlah historiografi tradisional yang dinarasikan dalam naskah-naskah (manuscripts) asal Cirebon, tidak sedikit yang menyinggung tentang moderasi beragama. Namun demikian, kecenderungan naskah babad mengalami pergeseran perspektif ketika memasuki era kolonialisme bangsa-bangsa Eropa. Narasi toleransi antar suku bangsa atau antar agama mengalami gesekan serius. Terdapat sebuah naskah yang berasal dari tradisi Cirebon, yang menarasikan secara implisit tentang moderasi beragama pada era-era awal perkembangan Islam dan kota-kota pelabuhan, yaitu Serat Carub Kandha. Artikel ini membahas tiga masalah terkait dengan moderasi beragama dalam Serat Carub Kandha, yakni: (1) konteks yang melatari penulisan dan penyalinan naskah Serat Carub Kandha; (2) narasi moderasi beragama dalam naskah Serat Carub Kandha; (3) Relevansinya bagi kehidupan beragama saat ini di Indonesia. Sumber yang dijadikan bahan primer penelitian adalah naskah Serat Carub Kandha koleksi Rafan Hasyim di Cirebon dalam tulisan Pegon. Dengan pendekatan filologis dan hermenutik, artikel ini menunjukkan bahwa Naskah Serat Carub Kandha menjadi bukti historis dan memori kolektif tentang praktik moderasi beragama di masa lalu Indonesia, khususnya di kawasan pesisir utara Jawa Barat. Narasi moderasi yang mengemuka adalah tentang sikap menghargai agama lain, akomodatif terhadap kebudayaan lokal, dan anti kekerasan.   Kata kunci: Cirebon, manuskrip Babad, moderasi beragama, Serat Carub Kandha